How Financial Ratios and Firm Size Affect Profitability: Evidence from Chemical Industry in Indonesia - Mirzatul Kadri; Zahara Muzaiyana; Wisnu Satria; Taufiq C. Dawood; Kamal Fachrurrozi; Ichwan Ichwan (Heca Sentra Analitika, 2025)
This study investigates the impact of financial ratios and firm size on the profitability of companies in the chemical industry listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023 . Profitability is measured using Return on Assets (ROA), while the independent variables include Working Capital to Total Assets (WCTA), Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TAT), and Firm Size (SZ). A quantitative approach was employed using multiple linear regression analysis. The sample consisted of 25 chemical companies selected through purposive sampling. The findings reveal that CR, TAT, and SZ have a significant positive effect on ROA, while DER has a significant negative effect. WCTA, however, shows no significant impact on profitability. The adjusted R² value of 0.742 indicates that 74.2% of the variation in profitability can be explained by the model. These results highlight the importance of liquidity management, efficient asset utilization, optimal capital structure, and firm scale in driving profitability in the chemical sector. The study provides valuable insights for company management, investors, and policymakers in enhancing financial performance and strategic decision-making within the industry.